Field measurement and evaluation of vibrations inside buildings above metro tunnels. Issue 166 (March 2023) - Di, Honggui; Su, Guangbei; Yu, Jiayong; Xu, Yonggang; Xu, Pingbao; Zhou, Shunhua
Abstract: The buildings above metro tunnels have developed rapidly in China in recent years because it can make comprehensive use of land resources. However, buildings are closer to the vibration source, which makes them sensitive to train-induced vibration and adversely affect the living quality of the building occupants. Based on field-measured vibration data of buildings above metro tunnels, the response characteristics of train-induced vibrations at the basement and floor slabs of buildings were investigated herein. The results showed that the vertical acceleration was much larger than the horizontal acceleration. The vertical acceleration of the floor slabs was greater than that of the basement, and the main frequency band of vertical vibration was 50–70 Hz. In this case, with an increase in the floor, the vertical acceleration of the buildings first increased, decayed rapidly, and finally increased slightly; that is, a vibration amplification phenomenon on the top three floors of the buildings was observed. The maximum vertical acceleration appeared on the 4th floor and the minimum vertical acceleration appeared on the floor, which was three floors below the top. The horizontal distance between the building and tunnel has a significant effect on the amplitude of vertical acceleration. The vibration levels caused by different trains have little difference, with a maximum variance of 2.3 dB. The Z vibration levels of all the measuring points were significantly lower than the first-level vibration limit (73 dB) specified in Chinese standard for limits and measurement methods of vibration in the room of residential building (GB/T 50355-2018) . Highlights: A field measurement for the train-induced vibrations in over-track buildings above metro tunnels was performed. The vertical acceleration of the floor slabs was greater than that of the basement, and the main frequency band was 50–70 Hz. The vertical acceleration of the buildings had a vibration amplification phenomenon on the top three floors. The vertical acceleration amplitude of the building is mainly affected by the distance between the building and tunnel. Vibration levels of over-track buildings were compared with standards.